Semiconductor Quantum Dots Surface Modification for Potential Cancer Diagnostic and Therapeutic Applications. (23rd October 2012) - Wang, Jidong; Han, Shumin; Ke, Dandan; Wang, Ruibing
Abstract : Semiconductor Quantum dots (QDs) have generated extensive interest for biological and clinical applications. These applications arise from their unique properties, such as high brightness, long-term stability, simultaneous detection of multiple signals, tunable emission spectra. However, high-quality QDs, whether single or core-shell QDs, are most commonly synthesized in organic solution and surface-stabilized with hydrophobic organic ligands and thus lack intrinsic aqueous solubility. For biological applications, very often it is necessary to make the QDs dispersible in water and therefore to modify the QD surfaces with various bifunctional surface ligands or caps to promote solubility in aqueous media. Well-defined methods have been developed for QD surface modification to impart biocompatibility to these systems. In this review, we summarize the recent progress and strategies of QDs surface modification for potential cancer diagnostic and therapeutic applications. In addition, the question that arose from QD surface modification, such as impact of size increase of QD bioconjugates after surface-functionalization or surface modification on photophysical properties of QDs, are also discussed.